Trump's US Policy, International Agreements and the Islamic Republic of Iran Foreign Policy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The foreign policy of countries is always shaped by the value system and national characteristics prevailing in them, forming their national identity as a nation-state, which is theorized and operationalized to ensure national interests and to reach short-term, medium-term and long-term goals. The US, as a superpower of the international system, and the Islamic Republic of Iran (IRI) as a regional power in the Middle East follow this rule too. The study aimed at explaining and examining the type of Trump's foreign policy of the US and that of IRI and their approach regarding international agreements using a descriptive-explanatory method and adopting a comparative approach within the framework of the theory of strategic foreign policy model. Moreover, the paper tried to answer the main question of whether Donald Trump's conflicting approach to international agreements and the withdrawal of the US from some of these agreements, like the Joint Comprehensive Plan of Action (JCPOA), is as a change in US macroeconomic strategy and the US tendency to isolate in international politics or not. The main hypothesis of the paper was that this kind of approach is solely a tactic to change the strategic goals of foreign policy of other countries, whether friend and enemy of the US to accept American hegemony in international politics by them and strengthening its superpower state in the international system. The paper first went through the introduction and literature, then the theoretical framework, US foreign policy during Trump's presidency and his approach to international agreements, the foreign policy of IRI and its approach to international agreements were reviewed to prove the hypothesis. Moreover, the results indicated that Iran should establish a bilateral monetary and banking mechanism with the European Union, like establishing a joint investment bank and a political and economic alliance with the Brazil, Russia, India, China, and South Africa (BRICS) countries to create a soft balance against the US by stress relieve with its regional rivals like Turkey and Saudi Arabia.